The Influence of Discussion Learning Methods on Student Learning Interests at SMKN 1 Watansoppeng - Arhas, Sitti Hardiyanti; Septian, Aryandi; Isgunandar, Isgunandar (Pinisi Journal of Education and Management, 2023)
This study aims to describe the use of the discussion learning method, the description of students' learning interests, and the effect of the discussion learning method on students' learning interest at SMKN 1 Watansoppeng. This research is a quantitative research with a symmetric associative ex-post facto design that uses descriptive and inferential statistical tools. the sample in this study amounted to 80 people with random sampling technique. Data collection techniques used are questionnaires, observation, and documentation. The data analysis technique used is descriptive and inferential statistical analysis. The test results show that the discussion learning method is in the very good category and the students' learning interest is in the good category. In the product moment correlation test, the relationship between variables is moderate and there is influence between the two variables. Based on the results of simple linear regression analysis, it was concluded that there was a positive and significant effect of the discussion learning method on students' learning interest at SMKN 1 Watansoppeng.